Analisis Kerjasama Peternakan Kambing Dengan Sistem Paruhan Di Desa Harimau Tandang Dalam Perspektif Fikih Muamalah - Riskiah, Desi Putri; Hanif, Ahmad (Journal of Fiqh in Contemporary Financial Transactions, 2024)
This research aims to determine the suitability of Muamalah Fiqh for Goat Farming cooperation: in accordance with the muamalah fiqh perspective, fulfilling the pillars and conditions and avoiding transactions that are prohibited by sharia. The descriptive qualitative research method uses field methods. Data collection techniques include observation and interviews. From this research it can be concluded that the contract used in part-time cooperation is the Mudharabah contract. This cooperation “paroan” in Harimau Tandang Village has fulfilled the Mudharabah pillars, but it has not fulfilled the requirements for each Mudharabah pillar.